Gender-Based Regional Development Strategy in Bone Regency - Mustika, Viki; Niswaty, Risma; Rifdan, Rifdan; H, Herman (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2024)
The success of development is highly dependent on the extent to which the balance of women's and men's participation in all aspects of life. This study aims to determine the strategy of gender-based regional development and to determine the determinant factors in the implementation of gender-based regional development programs in Bone Regency. This study uses a descriptive qualitative research method. Data collection techniques include literature studies, researchers study and review a number of written materials, both books, research results, articles and electronic journals. The data analysis technique uses Data Reduction, Data Presentation and Withdrawal. The results of the study indicate that the gender-based regional development strategy in Bone Regency. The determinant factors for the implementation of gender-based regional development programs in Bone Regency reduce the gap with each regional apparatus organization implementing gender-responsive planning within the work reference framework. Each program has been supported by regulations and cooperation between local governments, the Regional People's Representative Council, the Women's Empowerment and Child Protection Service, and the Bone Women's Empowerment Institute. This study can be used as a reference and decision-making material at the village level regarding regional development strategies.